The Students’ Perception of Small Group Discussion for Developing EFL Students’ Speaking Skills - Hadijah Hadijah; Musfirah Musfirah (ELT Worldwide: Journal of English Language Teaching, 2022)
The purposes of this research were to know the students’ speaking skill and perceptions about The small group discussion program in Intensive English Guidance Program (UPGRADING) who will joining the English program upgrading or intensive English Guidance and aims to determine students' perceptions about the small group discussion program in learning speaking skills. This research is a qualitative study with ten students as subjects and ten instructors. The instruments used were interview sheets and voice recordings. Interview sheets that were given to students as well as instructors were improved to see their perceptions of learning speaking skills. It was found that the students 'perceptions of the small group discussion program were good for the learning process of students' speaking skills in their English development, and also the instructors 'perceptions of the program were good in developing students' English, especially in their speaking skills where there was fluency, grammar, vocabulary, pronunuciation, and understanding although there are many perceptions about one aspect of speaking skills, namely that grammar is not able to develop their speaking skills towards the program but can fulfill all factors that are in the process of learning speaking skills . The data analysis method is was done by applying the procedures suggested by Miles and Huberman covering data condensation, data display, and verifying conclusion. The results showed that the students perception on small group discussion in learning speaking skill was the students can increase their speaking skill, the program effective for speaking skill learning process, the program is motivational for speaking learning process, the difficulties they face in speaking skill learning process through small group discussion program, and the instructors’ ways to handle the program have an affect on students improvement.